Farmer-led innovations and their role in entrepreneurship: a bibliometric exploration - Bikram Barman; Rashmi Singh (Discover Agriculture)
Abstract This study examines the global research landscape on farmer-led innovation and its role in advancing agricultural sustainability and entrepreneurship. Despite increasing recognition of farmer-driven approaches, the literature remains fragmented, calling for a systematic bibliometric analysis to understand its thematic evolution and scholarly development. Based on 397 articles retrieved from Scopus in January 2025, the study analyses leading contributors, institutional affiliations, publication sources, citation patterns, and keyword co-occurrence networks. The results reveal De Carvalho GDG and Gupta AK as influential authors, with Wageningen University and ICAR emerging as key institutions. Innovation, sustainability, smallholder farming, and local adaptation are among the most prominent research themes, with significant contributions from the United States, China, India, and the UK. The findings highlight the importance of grassroots knowledge, policy support, and technological integration in cultivating farmer-led innovation. Despite significant progress, regional disparities remain, emphasizing the need for more inclusive, interdisciplinary, and collaborative research efforts. Future research priorities include strengthening policy frameworks and promoting bottom-up innovation, particularly in under-represented regions.